THE OPTIMAL CONDITIONS FOR TOTAL SALINITY REMOVING FROM WATER USING NEW LOCAL HALOPHILIC BACTERIAL STRAINS - Salm, Ahmed S. A.; AL-Shamary, Elham (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to determine the optimal conditions for removing total salinity from an aqueous solution of known salt concentration 10% using four new bacterial strains that are tolerant to high salinity genetically diagnosed and registered in the international gene bank (NCBI). Modified nutrient broth medium (MNB) was used with the addition of 10% sodium chloride. The ability of the bacterial strains to remove total salinity was tested in terms of the decrease in total dissolved solids (TDS), where the highest removal rate was after 72 hours, at a temperature of 30°C, with an inoculum volume of 1.5% and a pH of 7. The removal rates were higher in static cultures in the same conditions compared to using the vibrating incubator at 100 rpm. The removal rate decreased when using a mixture of the cocci strain with the three other bacillus species, and the removal rates were constant when using a mixture of the bacillus strains. Total desalination rates were obtained using bacterial strains (A, B, C, and D) after applying the optimal conditions obtained from this study (94, 91, 90, and 92) %, respectively.